2022
DOI: 10.3389/fmed.2022.872725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Relationship Between SI and RASI Scores With the Outcome of Sepsis Patients

Abstract: The aim of this study was to compare the relationship between shock index (SI) and respiratory adjusted shock index (RASI) scores with the final outcome of sepsis patients referred to the emergency department. This was prospective research that examined individuals who had been diagnosed with sepsis, determined by the presence of at least two of the three quick sepsis-related organ failure assessment (qSOFA) criteria and the presence of an infectious disease based on a diagnosis made by a hospital physician of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several published studies have been conducted on the prognostic role of SI in predicting clinical outcomes of patients. For example, a recent prospective study showed that SI can predict the risk of death in patients with sepsis ( 21 ). Charles et al revealed that elevated SI in patients with severe sepsis in the emergency room may be an important indicator of disease escalation and risk of cardiovascular failure ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies have been conducted on the prognostic role of SI in predicting clinical outcomes of patients. For example, a recent prospective study showed that SI can predict the risk of death in patients with sepsis ( 21 ). Charles et al revealed that elevated SI in patients with severe sepsis in the emergency room may be an important indicator of disease escalation and risk of cardiovascular failure ( 22 ).…”
Section: Discussionmentioning
confidence: 99%